Paleoenvironment of the Central Himalaya during late MIS 3 using stable isotopic compositions of lacustrine organic matter occluded in diatoms and sediments. (30th August 2020) - Rahman, Abdur; Sarkar, Siddhartha; Kumar, Sanjeev
Abstract: Marine Isotope Stage (MIS) 3 was an interstadial stage in the climate history of the Earth where the last phase (40–30 ka) showed relatively warmer climate over the northwest China, Tibetan Plateau, and northwestern India compared to other regions of the world. However, not many studies are reported for climate variability during this period from the Himalayan region. Here, an attempt has been made to understand the paleoenvironment of the Central Himalaya during 45–29 ka using stable isotopic compositions of carbon (δ 13 CTOC ) and nitrogen (δ 15 NTN ) along with their elemental ratios (TOC/TN) in bulk organic matter and occluded organic matter within diatom frustules (δ 13 CDiatom ) of a paleolake sequence. The variabilities in δ 13 CDiatom, δ 13 CTOC, and TOC/TN ratios indicated intermittent changes in the lake carbon dynamics from bicarbonate dominated system to carbon dioxide dominated regime. These changes in lacustrine carbon cycling provided evidence for existence of sporadic dry events in the Central Himalaya during 45–29 ka. In agreement with the records from the northwest China, Tibetan Plateau, and northwestern India, our results also confirm the existence of a relatively wet and humid period during 40–32 ka in the Central Himalaya. Therefore, it appeared that compared to other parts of the world, relatively wet and humid climate existed throughout this region. However, the mechanism behind this wet and humid phase remains to be explored and warrants a high resolution paleoclimate study in the Himalaya.